2022
DOI: 10.1152/ajpheart.00189.2022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of breakthrough COVID-19 cases during the omicron wave on vascular health and cardiac autonomic function in young adults

Abstract: We show for the first time that breakthrough cases of COVID-19 during the Omicron wave does not impact vascular health and cardiac autonomic function in young adults. These are promising results considering earlier research showing impaired vascular and autonomic function following previous variants of COVID-19. Collectively, these data demonstrate that the recent Omicron variant is not detrimental to cardiovascular health in young, otherwise healthy, vaccinated adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 21 publications
5
44
0
Order By: Relevance
“…However, we were unable to recapitulate these findings in young adults, even when considering their symptomatology. Taken together with the findings from our previous work during the omicron wave ( 5 ), this suggests that cardiac autonomic function may be less susceptible to change following COVID-19 in young healthy adults. Middle-aged adults with persistent symptoms (e.g., fatigue) were observed to be more likely to experience orthostatic intolerance ( 3 , 19 ), which would support the notion that symptomology may matter when it comes to autonomic dysfunction.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…However, we were unable to recapitulate these findings in young adults, even when considering their symptomatology. Taken together with the findings from our previous work during the omicron wave ( 5 ), this suggests that cardiac autonomic function may be less susceptible to change following COVID-19 in young healthy adults. Middle-aged adults with persistent symptoms (e.g., fatigue) were observed to be more likely to experience orthostatic intolerance ( 3 , 19 ), which would support the notion that symptomology may matter when it comes to autonomic dysfunction.…”
Section: Discussionsupporting
confidence: 80%
“…Participants also completed the International Physical Activity Questionnaire (IPAQ) ( 10 ) to assess their physical activity levels during the week before testing. Resting HRV and cardiac BRS data were previously reported for eight participants in the control group ( 5 ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The results of a recent study showed that vascular function was not impaired in participants who had been vaccinated against COVID-19 but were infected with the Omicron variant of SARS-CoV-2 [ 34 ]. Skow et al measured FMD and cfPWV in 23 vaccinated adults with mild-to-moderate COVID-19 (Omicron) who did not require hospitalization and 13 vaccinated healthy controls without a history of COVID-19 [ 34 ]. The average period from the diagnosis of SARS-CoV-2 infection to FMD measurements was 30 ± 9 days.…”
Section: Covid-19 and Vascular Functionmentioning
confidence: 99%